2017
DOI: 10.1186/s40795-016-0122-2
|View full text |Cite
|
Sign up to set email alerts
|

Different forms of malnutrition among under five children in Bangladesh: a cross sectional study on prevalence and determinants

Abstract: Background: This empirical study investigated the extent of malnutrition and factors associated with malnutrition amid children aged 0-59 months in Bangladesh using Bangladesh Demographic Health Survey data, 2014. Methods: To examine the extent of malnutrition among the children under five in Bangladesh, we used Height-forage, weight-for-height and weight-for-age. The association between the selected factors and nutritional status were assessed and logistic regression models were fitted for the three indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

61
132
4
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(216 citation statements)
references
References 23 publications
61
132
4
5
Order By: Relevance
“…This study found that age of the child significantly affected the child's nutritional status. This finding is consistent with findings from studies in Ethiopia and Bangladesh [23,26,32,33] which found out that risk of undernourishment increased along with increase in the age of a child. This is attributable to late introduction of supplementary food with low nutritional quality [34].…”
Section: Discussionsupporting
confidence: 92%
“…This study found that age of the child significantly affected the child's nutritional status. This finding is consistent with findings from studies in Ethiopia and Bangladesh [23,26,32,33] which found out that risk of undernourishment increased along with increase in the age of a child. This is attributable to late introduction of supplementary food with low nutritional quality [34].…”
Section: Discussionsupporting
confidence: 92%
“…Children of illiterate fathers were at more than three times higher risk of stunting compared to educated fathers. This finding is also in line with the findings of the study from Bangladesh [13] and other studies [32][33][34][35][36]. Possibly, this might be due to the fact that households with educated fathers have a greater likelihood of having a higher income, since fathers are the main source of income for the households studied.…”
Section: Discussionsupporting
confidence: 91%
“…The household wealth of the family of the subject children was associated with stunted growth in this study. This finding is in line with other findings from analysis of the Mini Ethiopian Demographic and Health Survey data [15], a cross sectional study conducted on prevalence and determinants malnutrition in Bangladesh [13], and another study from Sindh, Pakistan [14]. The primary influence of household wealth is on child feeding practices related to an inadequate amount of food and the nutritional content of meals, which affect the nutritional status of children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study of undernutrition is important because it is a problem that continues to affect thousands of people worldwide . There is a specific period in which the occurrence of undernutrition leads to more severe damage, known as the critical period of development.…”
Section: Introductionmentioning
confidence: 99%